Effect of t2g-Correlations and Doping in CrSBr Ferromagnetic Semiconductor - Luis Craco; Sabrina Silva Carara (Condensed Matter)
We perform a comprehensive analysis of the correlated electronic structure reconstruction of the ferromagnetic CrSBr van der Waals (vdW) bulk crystal. Using generalized gradient approximation combined with dynamical mean-field theory, we show the minor role played by multi-orbital electron–electron interactions in semiconducting CrSBr. Our study is relevant to understanding the electronic structure within the <semantics>Cr3+</semantics> oxidation state with strongly spin-polarized <semantics>t2g</semantics> orbitals and should be applicable to other ferromagnetic vdW materials from bulk down to the low-dimensional limit. This work is relevant for understanding orbital and spin selectivity and its link to the memristor current–voltage characteristic of CrSBr for future neuromorphic computing.